DEVELOPMENT OF THE DATA TRANSFERING SYSTEM USING SOC - Malcheva, Raisa; Naaem, Hazim (European Scientific Journal, ESJ, 2014)
The aim of work was analyzes of SoC and design of the wireless data transfer system. The modern industrial control systems and technologies connected to design of data transfering systems are analyzed. Advantages of implementation of such systems on FPGA are described. The Dispatching automation system "KARJER" is described. System controls navigational parameters (coordinates, speed) of vehicles as well as condition of onboard equipment like truck body load and amount of fuel left in its fuel tank. Information gets collected using GPS technologies.To improve the parameters of this system for determination of objects positions it was proposed to receive data from several sources and send them to the user by means of GSM modules and short messages of the SMS. Design of data transfering system is considered. It constructs of two serial input-output ports to exchange data with GPS and GSM modules and processor. For programming and simulation of the main blocks of the transfering system the following software are used: Xilinx ISE Design Suite; Aldec Active HDL; Quartus II Web Edition. To develop and test the board Xilinx Spartan-3E Starter Kit and software Xilinx ISE Design suite are used. Results of HDL simulation of developed system are shown. The developed controller can be used as basic for development of industrial devices of specialized assignment; the received results also can be used as a bright example for the students training.